12-[12-(12:6+6)-12:6]-12:12.
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
12 - [ 12 - ( 12 : 6 + 6 ) - 12 : 6 ] - 12 : 12 = 9
12 - [ 12 - ( 2 + 6 ) - 12 : 6 ] - 12 : 12 =
12 - ( 12 - 8 - 12 : 6 ) - 12 : 12 =
12 - ( 12 - 8 - 2 ) - 12 : 12 =
12 - ( 4 - 2 ) - 12 : 12 =
12 - 2 - 12 : 12 =
12 - 2 - 1 =
10 - 1 = 9
davstefbully:
ok
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă